Extensive diversity and inter-genepool introgression in a world-wide collection of indeterminate snap bean accessions - Blair, Matthew W.; Chaves, A.; Tofiño Rivera, Adriana Patricia; Palacio Mejia, JD; Calderón Sotelo, J.F. (Springer, 2010)
Common bean can be grown as a grain crop (dry beans) or as a fresh vegetable (snap beans/green beans), both items being important in nutritional terms for providing essential minerals and vitamins to the diet. Snap beans are thought to be derived predominantly from dry beans of the Andean genepool and to be of a recent European origin; however, the existence of Mesoamerican genepool characteristics especially in traditional indeterminate growth habit snap beans indicates a wider origin. The objective of this study was to evaluate genetic diversity within a set of 120 indeterminate (pole type) snap beans and 7 control genotypes representing each genepool using amplified fragment length polymorphism (AFLP) and simple sequence repeat or microsatellite (SSR) markers. The genotypes were predominantly from Asia, Europe and the United States but included some varieties from Latin America and Africa. AFLP polymorphism ranged from 53.2 to 67.7% while SSR polymorphism averaged 95.3% for the 32 fluorescent and 11 non-fluorescent markers evaluated and total expected heterozygosity was higher for SSR markers (0.521) than for AFLP markers (0.209). Both marker systems grouped the genotypes into two genepools with Andean and Mesoamerican controls, respectively, with the Mesoamerican group being predominant in terms of the number of genotypes assigned to this genepool. Phaseolin alleles were not tightly associated with genepool assignment indicating that introgression of this locus had occurred between the genepools, especially with phaseolin “S” in the Andean group (23.5%) and phaseolins “T” and “C” in the Mesoamerican group (12.2 and 8.2%, respectively). The implications of these results on the origin of pole type snap beans and on breeding strategies for this horticultural crop are discussed.